2009
DOI: 10.1021/bi9015988
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the Class C β-Lactamase from Acinetobacter spp.: Insights into Effective Inhibitor Design

Abstract: The need to develop β-lactamase inhibitors against class C cephalosporinases of Gram-negative pathogens represents an urgent clinical priority. To respond to this challenge, five boronic acid derivatives including a new cefoperazone analog were synthesized and tested against the class C cephalosporinase of Acinetobacter baumannii (Acinetobacter-Derived Cephalosporinase, ADC). The commercially available carbapenems antibiotics were also assayed. In the boronic acid series, a chiral cephalothin analog with a met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 68 publications
4
42
0
Order By: Relevance
“…In the case of meropenem, we also observed an adduct that was 43 Ϯ 3 amu less than the main species (⌬ ϩ340 Ϯ 3 Da). This secondary product is reminiscent of what has been seen in other ESI-MS analyses of inactivation of class A and class C enzymes by carbapenems, and we suspect it represents loss of the C 6 ethoxy group (17,20,25). Tryptic digestion.…”
Section: Vol 55 2011 Ctx-m-9 Inhibition By ␤-Lactamase Inhibitors 3469supporting
confidence: 58%
See 1 more Smart Citation
“…In the case of meropenem, we also observed an adduct that was 43 Ϯ 3 amu less than the main species (⌬ ϩ340 Ϯ 3 Da). This secondary product is reminiscent of what has been seen in other ESI-MS analyses of inactivation of class A and class C enzymes by carbapenems, and we suspect it represents loss of the C 6 ethoxy group (17,20,25). Tryptic digestion.…”
Section: Vol 55 2011 Ctx-m-9 Inhibition By ␤-Lactamase Inhibitors 3469supporting
confidence: 58%
“…The turnover number (t n ) or the partitioning of the initial enzyme-inhibitor complex between hydrolysis and enzyme inactivation, k cat /k inact (partition ratio), was determined as previously reported (2,17,53).…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown analogs of ampicillin, cephalothin, and cefoperazone to be inhibitors of clinically relevant class A and C ␤-lactamases in the nM range (i.e., 9.3 nM, 420 nM, and 11 nM for K. pneumoniae SHV and for AmpCs from P. aeruginosa and Acinetobacter spp., respectively) (Fig. 3b) (53)(54)(55)(56). These compounds are still preclinical.…”
Section: Boronic Acid ␤-Lactamase Inhibitorsmentioning
confidence: 97%
“…The ceftazidime BATSI and cefoperazone BATSI analogues ( Fig. 1) were synthesized as previously described (7). Compounds 1 and 2 were obtained in two steps according to the scheme shown in Fig.…”
Section: Synthesis Of Boronic Acid Inhibitorsmentioning
confidence: 99%
“…Compounds 1 and 2 were obtained in two steps according to the scheme shown in Fig. 1B by using the appropriate amino acids (D-homotyrosine, synthesized as hydrobromide from D-aspartic acid [15,28], and commercially available D-tyrosine, respectively), commercially available 4-ethyl-2,3-dioxopiperazine-1-carbonyl chloride, and bis-(trimethylsilyl)-aminomethaneboronate, synthesized as previously described (7).…”
Section: Synthesis Of Boronic Acid Inhibitorsmentioning
confidence: 99%